2014
DOI: 10.3171/2014.5.jns131872
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of outcome in civilians with gunshot wounds to the head upon presentation

Abstract: Object Prediction of outcome from initial presentation after a gunshot wound to the head (GSWH) is essential to further clinical decision making. The authors' goals are to report the survival and functional outcomes of these patients, to identify prognostic factors, and to propose a scoring system that can predict their outcome. Methods The records of 199 patients admitted with a GSWH with dural penetration between 1990 and 2008 were retrospectively reviewed. The inclusion criterion was a CT scan available fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
85
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 27 publications
7
85
0
Order By: Relevance
“…The mean score on the St. Louis Scale for Pediatric Gunshot Wounds to the Head in children who survived and those who died was 2.8 (range 0-12) and 10 (range [3][4][5][6][7][8][9][10][11][12][13][14], respectively. Table 5 shows the average scores and range for the survivors by GOS score.…”
Section: St Louis Scale For Pediatric Gunshot Wounds To the Headmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean score on the St. Louis Scale for Pediatric Gunshot Wounds to the Head in children who survived and those who died was 2.8 (range 0-12) and 10 (range [3][4][5][6][7][8][9][10][11][12][13][14], respectively. Table 5 shows the average scores and range for the survivors by GOS score.…”
Section: St Louis Scale For Pediatric Gunshot Wounds To the Headmentioning
confidence: 99%
“…8,9,18,28,30 The St. Louis scale is the only one that we know of that is specific for children and marks a significant contribution to the literature. 2 In Bandt and colleagues' series, a St. Louis scale score ≤ 4 was associated with a positive predictive value of 88.9% for survival; a score ≥ 5 was associated with a negative predictive value of 96.7% for death.…”
Section: St Louis Scale For Pediatric Gunshot Wounds To the Headmentioning
confidence: 99%
“…[5] Çırak et al [19] have reported that a patient's prognosis can be predicted on the basis of CT findings and GCS. Aarabi et al [22] and Hoppe et al [39] have reported mean admission GCSs of 7.8 and 13.5, respectively. They noted that GCS was inversely proportional to prognosis.…”
Section: Discussion Concerning Emergency Procedures Applied For Faismentioning
confidence: 99%
“…[4][5][6] Thus, among the estimated 5.3 million people living in the US with traumatic brain injury (TBI)-related disability, the proportion of gun-shot wound survivors has been rising steadily. 3,[7][8][9][10][11] Among head injuries, penetrating injuries (PTBI) are associated with the worst outcomes. 12,13 and no effective restorative treatment beyond physical therapy is currently available to mitigate post-TBI disability.…”
Section: Introductionmentioning
confidence: 99%